Chemistry : - Moore, John W. (Brooks/Cole-Thomson Learning, 2005)
The text has good coverage, high pedagogy, nice graphics and a solid style. The nanochemistry material is a great selling point to the engineers. The Moore text was chosen for the quality and level of writing; the level and variety of end-of-chapter problems; the emphasis on developing a conceptual understanding of atomic systems; and the integration of biochemistry, organic, and environmental topics throughout.